Assessment of donor satisfaction as an essential part of living donor kidney transplantation: an eleven‐year retrospective study. (10th September 2018) - Menjivar, Ana; Torres, Xavier; Paredes, David; Avinyo, Nuria; Peri, Josep Maria; De Sousa‐Amorim, Erika; Oppenheimer, Federico; Manyalich, Marti; Diekmann, Fritz; Revuelta, Ignacio
Summary: Living kidney donors seem highly satisfied with donation. However, previous studies measure satisfaction by a single‐item or by simply questioning donors' willingness to donate again or to recommend living donation. With the aim of analyzing whether satisfaction with donation is a multidimensional construct, thus allowing a more specific characterization of dissatisfied donors, 332 living kidney donors (2005–2015) answered a renewed version of the European Living Donation and Public Health Project satisfaction survey. Exploratory factor‐analyses suggested that satisfaction was composed of three‐factors: violation of donors' expectancies about donation; interference of donation on daily activities, and pain and discomfort. Donors reported high levels of satisfaction. However, cluster‐analysis identified a subgroup characterized by a higher discrepancy between the expected and the actually experienced during donation, higher interference on daily activities, and higher pain and discomfort. Most of them considered that hospital discharge was premature, suffered economic losses and perceived worse health outcomes of their recipients. Single questions assessing donors' willingness to donate again or to recommend living donation were unable to differentiate between clusters. In summary, donor's satisfaction seems better characterized by three dimensions than by single questions.